2018
DOI: 10.1371/journal.pone.0195303
|View full text |Cite
|
Sign up to set email alerts
|

Childhood behavioral inhibition is associated with impaired mentalizing in adolescence

Abstract: Recent advances suggest that impairment in social cognition (SC) may play a role in the development of social anxiety (SA). However, very few studies have analyzed whether SA fosters poorer social-cognitive development as it leads to social avoidance. This study aimed to analyze whether retrospectively assessed behavioral inhibition (BI) (i.e., an early form of SA) in childhood is associated with a deficit in social cognition operationalized as impairment of mentalizing (MZ) in adolescence. A sample of 256 ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 98 publications
(114 reference statements)
3
11
0
Order By: Relevance
“…This resonates with data suggesting that mentalizing deficits are linked with the level of interpersonal withdrawal in patient samples (Frith, 2014;Sergi et al, 2007;Weijers et al, 2018). Our results are also consistent with recent findings demonstrating links between diminished mentalizing capacities in adolescence and retrospective reports of social anxiety in childhood (Ballespí, Pérez-Domingo, Vives, Sharp, & Barrantes-Vidal, 2018). Young people who withdraw from interpersonal contact in the context of social anxiety, may encounter less social interaction opportunities, essential for developing a capacity to understand mental states (Banerjee & Henderson, 2001).…”
Section: Associations Between Schizotypal Personality Features and Mentalizingsupporting
confidence: 92%
“…This resonates with data suggesting that mentalizing deficits are linked with the level of interpersonal withdrawal in patient samples (Frith, 2014;Sergi et al, 2007;Weijers et al, 2018). Our results are also consistent with recent findings demonstrating links between diminished mentalizing capacities in adolescence and retrospective reports of social anxiety in childhood (Ballespí, Pérez-Domingo, Vives, Sharp, & Barrantes-Vidal, 2018). Young people who withdraw from interpersonal contact in the context of social anxiety, may encounter less social interaction opportunities, essential for developing a capacity to understand mental states (Banerjee & Henderson, 2001).…”
Section: Associations Between Schizotypal Personality Features and Mentalizingsupporting
confidence: 92%
“…However, the factor structure of MZQ is not consistent ( Paridaens, 2017 ; Song and Choi, 2017 ), and our sample size was too small to increase the number of variables and separately investigate the predictive power of different mentalization types. Therefore, like other studies, we decided to include the total MZQ score as a single measure ( Ballespi et al, 2018 ; Hayden et al, 2018 ; Probst et al, 2018 ). Future studies with larger samples may also investigate multiple facets of mindfulness (i.e., observing, describing, acting with awareness, non-judgmental, and non-reactive) and its relationship with schizotypy ( Baer et al, 2006 ) by combining questionnaire data with results from structured interviews and real-life observations.…”
Section: Discussionmentioning
confidence: 99%
“…Primary school children with social anxiety had difficulties in understanding the links between emotions, intentions, and beliefs in social situations, and were rated as having lower social skills that require insight into others' mental states (Banerjee & Henderson, 2001). Social anxiety in school predicted mentalizing deficits in adolescence (Ballespí et al, 2018). Others, however, found that both low and high levels of mind reading are related to social anxiety symptoms as a function of the individual's clinical anxiety level.…”
Section: Tom and Anxietymentioning
confidence: 99%